Employee Performance: Workload, Compensation and Employee Placement with Motivation as an Intervening Variable at the Pengadilan Tinggi Padang - Ayu Mardhiyah, Putri; Pawirosumarto, Suharno; Zefriyenni, Zefriyenni (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to identify the impact of Workload, Compensation and Employee Placement on Employee Performance through Motivation as an intervening variable at the Pengadilan Tinggi Padang. The research method employed involves sampling from a population of 114 employees at the Pengadilan Tinggi Padang, consisting of 94 Civil Servants (PNS) and 20 Non-PNS employees. From this population, a sample of 94 Civil Servants was selected for the study. Primary data was collected through questionnaires distributed to the 94 respondents. Data analysis was performed using SmartPLS 4 with Partial Least Squares (PLS) based Structural Equation Modeling (SEM). The results of this study indicate that: (1) Workload has a positive and significant effect on Motivation. (2) Compensation has a positive and significant effect on Motivation. (3) Employee Placement has a positive but not significant effect on Motivation. (4) Workload has a negative and significant effect on Employee Performance. (5) Compensation has a positive but not significant effect on Employee Performance. (6) Employee Placement has a positive and significant effect on Employee Performance. (7) Motivation has a positive and significant effect on Employee Performance. (8) Workload has a positive but not significant effect on Employee Performance through Motivation as an intervening variable. (9) Compensation has a positive and significant effect on Employee Performance through Motivation as an intervening variable. (10) Employee Placement has a positive but not significant effect on Employee Performance through Motivation as an intervening variable. (11) The contribution of Workload, Compensation, and Employee Placement to Motivation is 0.454 or 45.4%, while the remaining is influenced by other variables not examined in this study. (12) The contribution of Workload, Compensation, Employee Placement, and Motivation to Employee Performance is 0.449 or 44.9%, while the remaining is influenced by other variables not examined in this study.